Perancangan Sistem Informasi Rental Mobil dan Integrasi Payment Gateway Midtrans - Attaya Fiqri Pradana; Isnardi Isnardi; Hadadd Sammir; Khairil Hamdid (Prodi Sistem Informasi Universitas Dharma Andalas, 2026)
PT. Nabil Rental Mobil Padang currently does not have its own information system and still relies on a manual system, and has not yet integrated the Midtrans payment gateway. All data and transactions are still recorded manually in a book, resulting in customers not receiving up-to-date information on car availability, slow processes, and a high risk of human error. This research aims to design a Car Rental Information System with Payment Gateway Integration to enable the business owner to offer online booking, electronic payment, and more effective inventory management. Data collection methods used include field research, library research, and laboratory research using the PHP programming language, the Laravel 12 framework, and a MySQL database. System development follows the waterfall model, consisting of requirements analysis, system design, implementation and unit testing, system integration and testing, and operation and maintenance. The results show that the system was successfully built and all features function as intended, effectively addressing the issue of inaccurate vehicle information, improving operational efficiency, and enhancing payment transaction security.